فعالية استخدام وسائل نص القصة لترقية مهارة القراءة - Syarifah Rahmi; Zainal Abidin Hajib; Teuku Sanwil; Wardiah (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2022)
The problems faced by the students are that many teachers use traditional teaching aids, and this causes the ability of the students to comprehend the reading skill to be weak and they cannot understand the read texts. As for the objectives of the research, to know the process of teaching the skill of reading before applying the means of the text of the story in the private Islamic middle school, Nour Al-Rashad Al-Aziziya, and to know the extent of the effectiveness of using the means of the text of the story to improve the skill of reading. The research method used by the researcher was the procedural approach. To collect data, the researcher observed and provided the pre and posttest, and the researcher continued the two cycles. As for the results of the research, the process of teaching and learning the skill of reading was in agreement with the steps of applying the means of the story text and its steps. The teacher chooses the subject of the educational materials such as the reading texts, who may cut it by breaking the papers as the total number of students, and the use of the means of the text of the story in the process of teaching and learning the skill of reading is effective based on The result of the average for students from the second round obtains the criteria for the results of the completion limit, which means 86 in the percentage of 100% for the excellent.